The Effect of Disease Modifying Therapies on Disability Progression in Multiple Sclerosis: A Systematic Overview of Meta-Analyses - Claflin, Suzi B.; Broadley, Simon; Taylor, Bruce V. (Frontiers in Neurology, 2019)
Background: Disease modifying therapy (DMT) efficacy trials make an essential contribution to the development of evidence-based clinical treatments and practices for people with multiple sclerosis (MS). Meta-analysis is a critical part of this process and provides a powerful tool to assess the effects of DMT on MS progression. However, although there have been several meta-analyses on the effect of DMT on MS disease progression, they often do not reach the same conclusions. Objective: Our aim was to better understand and contextualise the results of meta-analyses evaluating DMT, identify differences in methodology that might explain their differing conclusions, and highlight areas for future research that will improve our ability to develop clinical recommendations. Methods: We conducted an overview of systematic reviews with meta-analyses assessing the efficacy of DMT on disability progression in people with MS in PubMed (Medline) and the Cochrane Database of Systematic Reviews. Results: We included 22 meta-analyses in this overview: eight general (on >3 DMT), 11 specific (on ≤3 DMT), 2 that evaluated subsets, and 1 that evaluated long-term effects. We found that there is good evidence that DMT improve short-term (≤2-3 years) disability progression outcomes relative to placebo in people with relapsing-remitting MS. However, results varied substantially between meta-analyses, and there is little evidence of their efficacy in other populations or over longer periods. The relative effects of individual DMT also remain unclear. The variance in results between meta-analyses may be related to the substantial differences in inclusion criteria, which was reflected in the limited overlap in included studies, as well as the year of meta-analysis publication. Of the 123 total unique studies included in the general meta-analyses, 77 (62.6%) were included in only one meta-analysis. This incongruence was also evident in the included DMT. Six of the 16 (37.5%) DMT evaluated in the general meta-analyses were only included in one meta-analysis. Conclusions: Translating DMT efficacy studies into evidence-based clinical practice requires greater methodological consistency in meta-analyses, more data on the relative effects of DMT through head-to-head clinical trials, and better reporting of adverse events.